Characterization of Ionosphere-Thermosphere Coupling from the VISIONS-2 Mission - Wilson, Kieran (Graduate Studies, 2023)
VISIONS-2 was a NASA sounding rocket mission consisting of two payloads flown on December 7th, 2018 from Svalbard, Norway. On board the first Visions-2 payload, electrostatic analyzers gathered data on low-energy ions throughout the flight. Existing in situ studies of the mechanics of ionosphere-thermosphere coupling within the undersampled E-region are limited. The present study aims to bolster these existing findings by characterizing the transition from collisionless to collision-dominated ionosphere-thermosphere interaction peaking near 120 km altitude, estimating the altitude at which friction balances the Lorentz force on ionospheric ions. For the purposes of this study, ion drift is estimated at regular altitude intervals throughout the transition region using two-dimensional images gathered by the electrostatic analyzers. In the absence of thermospheric wind measurements and low-altitude electric field measurements, the ion drift variation with altitude is used as a proxy measurement for neutral winds and the guiding centre drift. This approach prohibits the direct exploration of the effects of payload potential or ion species on the measured ion velocity. Study results place the collisional transition height below 120 km, corroborating previous research that constrains the collisional transition height, during quiet conditions, between 110 – 120 km.